2023
DOI: 10.3390/jcm12041454
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome: Etiology, Current Management, and Future Therapeutics

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder, typically characterized by anovulation, infertility, obesity, insulin resistance, and polycystic ovaries. Lifestyle or diet, environmental pollutants, genetics, gut dysbiosis, neuroendocrine alterations, and obesity are among the risk factors that predispose females to PCOS. These factors might contribute to upsurging metabolic syndrome by causing hyperinsulinemia, oxidative stress, hyperandrogenism, impaired folliculogenesis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 156 publications
4
26
0
Order By: Relevance
“…In addition, lower adherence to a healthy diet as lower dietary quality which has been observed among women with a history of GDM compared with women without a history of GDM may have also contributed to this (32). Similarly, we also found that lifestyle interventions more effective in lowering GDM risks in women without a history of PCOS, a population characterised by high insulin resistance (33). In addition to the physiological challenges of insulin resistance, women with PCOS may also face further challenges with adhering to a healthy lifestyle which range from physiological barriers such as alteration in gut hormone regulation to psychological barriers such as a high prevalence of disordered eating in this population (34).…”
Section: Discussionsupporting
confidence: 56%
“…In addition, lower adherence to a healthy diet as lower dietary quality which has been observed among women with a history of GDM compared with women without a history of GDM may have also contributed to this (32). Similarly, we also found that lifestyle interventions more effective in lowering GDM risks in women without a history of PCOS, a population characterised by high insulin resistance (33). In addition to the physiological challenges of insulin resistance, women with PCOS may also face further challenges with adhering to a healthy lifestyle which range from physiological barriers such as alteration in gut hormone regulation to psychological barriers such as a high prevalence of disordered eating in this population (34).…”
Section: Discussionsupporting
confidence: 56%
“…Studies have shown that hyperglycaemia, hyperinsulinemia and increased oxidative stress associated with poor dietary choices contribute to PCOS, though the precise mechanism of insulin dysregulation remains unknown. 27 RP6 H emphasised the link between obesity and PCOS, a connection supported by various studies. Obesity is reported to exacerbate metabolic complications associated with PCOS.…”
Section: Resultsmentioning
confidence: 87%
“…77 While PCOS is primarily a hormonal disorder with a genetic component, there is some evidence to suggest that exposure to certain environmental pollutants, such as EDCs and PAHs, may play a role in the development or worsening of PCOS. 78,79 EDCs and pollutants can potentially affect hormonal balance, insulin resistance and inflammation, all of which are associated with PCOS. 80 Individuals with endometriosis, PCOS or infertility may face compounded challenges when exposed to environmental pollution.…”
Section: Th E I M Pac T Of Pol Lu Tion On Hor Mona L Disru P Tionmentioning
confidence: 99%
“…There is some overlap between endometriosis and PCOS, as both conditions can contribute to irregular menstrual cycles and infertility 77 . While PCOS is primarily a hormonal disorder with a genetic component, there is some evidence to suggest that exposure to certain environmental pollutants, such as EDCs and PAHs, may play a role in the development or worsening of PCOS 78,79 . EDCs and pollutants can potentially affect hormonal balance, insulin resistance and inflammation, all of which are associated with PCOS 80 .…”
Section: The Impact Of Pollution On Hormonal Disruptionmentioning
confidence: 99%